The synthesis of novel polymer-bound calix[4]arenes - Barata, Patrícia (2020)
Two simple and efficient procedures for the synthesis of linear and cross-linked polymers containing hydrophobic and hydrophilic lower rim derivatives of p-tert-butylcalix[4]arenes are described. The target polymers were prepared either through the direct attachment of 25,26,27,28-tetrahydroxy-p-tert-butylcalix[4]arene (1), or its tripropoxy (2) and tetracarboxymethoxy (4) derivatives, to light cross-linked Merrifield's resins (1–2% DVB) or via radical addition copolymerisation of 25,26,27-tripropoxy-28-(4-vinyl-benzyloxy)-p-tert-butylcalix[4]arene (11) with styrene and a cross-linking agent.